(untitled) (Bangladesh Journal of Medical Science, 2021)
Intussusception, invagination of a segment of the gut into an adjacent one, is a relatively common cause of the intestinal obstruction in children but a very rare and uncommon clinical entity in the adults accounting to 1% and near about 65% of these are caused by malignant lead point. The Lipomatous polyp accounts for 4% of all benign tumors of the gut. In most of the cases, these are seen particularly in large intestine, usually sub mucosal and around ileocecal valve. These are mostly and very often asymptomatic. Mrs. Rahima Begum aged 65 years, previously was a healthy Bangladeshi housewife, with the history of recurrent abdominal colic of moderate intensity for the last 6 months, associated with the appearance of mass in the right lower quadrant with features of sub-acute intestinal obstruction got admitted into the Ibn Sina Medical College Hospital, Kallyanpur, Dhaka, Bangladesh. The required and most relevant investigations revealed the Ileocolic intussusception and underwent the right hemicolectomy. Postoperative recovery of the patient was uneventful excepting the hypertension only. Histopathology investigations revealed lipomatous polyp arising from the Ileocecal junction. This study reports intussuception in the adult due to lipomatous polyp, a very rare case presenting with sub acute intestinal obstruction. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.204-207